How your house works : a visual guide to understanding & maintaining your home - Wing, Charles, 1939- (Hoboken, N.J. : Wiley, 2012)
'An easy-to-understand richly illustrated guide to how everything in a house works. The book's many full-color illustrations are all drawn by the author for the general consumer to understand. Virtually everything in your house is included, with illustrated guidance on electrical systems, heating and air conditioning, plumbing, major household appliances, foundation, framing, doors, and windows. This updated second edition has considerable additional information, with new chapters related to sustainability and outside the house, as well as new topics including clock thermostats, ventless gas heaters, moisture and mold, and passive solar heating'--
Includes index.
Keywords: Dwellings -- Maintenance and repair; Electronic books